Analysis of Business Sustainability Influence in the Kediri Regency - Yosua Pamungkas Jaya; Sigit Puji Winarko; Mar’atus Solikah (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
MSMEs, or Micro, Small, and Medium Enterprises, are businesses that operate on a micro to medium scale. The presence of MSMEs plays a significant role in improving the welfare of communities in their immediate environment. Additionally, MSMEs also contribute to the economic growth of Indonesia as a nation. Considering the importance of their role, it is hoped that every MSME maintains consistent business sustainability. However, in reality, many MSMEs only survive for a short period due to various issues that are not promptly addressed, leading to eventual closure. Moreover, not all MSMEs possess the necessary capabilities to overcome these challenges. Based on these issues, a study was conducted to examine variables that can impact business continuity. The research aims to determine the influence of Selling Price, Promotion, Financial Literacy, and Accounting Information Systems on Business Sustainability. In processing the data, the researchers employed Multiple Linear Regression analysis, Partial t-test, and Simultaneous F-test. The results of the study indicate that variables such as selling price, promotion, financial literacy, and accounting information systems have an influence on business sustainability, both individually and collectively.